Pengaruh Kinerja Guru SMP Negeri di Kecamatan Pasaman Kabupaten Pasaman Barat - Nofrina M (Indonesian Institute for Counseling, Education and Therapy (IICET), 2015)
This study aims to analyze (1) the principal effect of leadership style on organizational climate junior high school teacher in District Pasaman, (2) influence of the leadership style of the principal motivatian of teachers working in the District Pasaman SMP N, (3) effect of principal leadership style on performance of junior high school teacher in District Pasaman SMP N, (4) the effect of organizational climate on work motivation of teacher in District Pasaman SMP N, (5) organizational climate influence on the performance of junior high school teacher in District Pasaman N, ( 6) effect of motivation on teacher performance of junior high school in District Pasaman.Based on the result of the study can be seen that, (1) the principal’s leadership style significantly influence the organizational climate in Kecamatan Pasaman SMP N, (2) the principal’s leadership style significantly influence the motivatian of teachers working in the District Pasaman SMP N, (3) leadership style principal significantly effect the performance of junior high school in District Pasaman N, (4) organizational climate significantlyinfluence the motivation of teacher working in the District Pasaman SMP N, (5) organizational climate had no significant effect the performance of junior high school teachers in Kecamatan Pasaman N, (6) Motivation significantly effect on the performance of junior high school teacher in District Pasaman.